PENGEMBANGAN PERANGKAT PEMBELAJARAN YANG BERFOKUS PADA CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK - Sulaiman, Ayu Zulpiah; Afdalia, Afdalia; Rosita, Rosita; Anggriani, Sri (Karst: Jurnal Pendidikan Fisika dan Terapannya, 2023)
This research represents an effort in research and development with the main objectives of (i) developing a reliable and valid contextual-based learning tool, (ii) assessing the improvement of students' critical thinking skills after being taught using the developed tool, and (iii) evaluating students' responses to the learning tool. The developed learning tool includes Lesson Implementation Plans (RPP), Student Learning Materials (BAPD), and Student Activity Sheets (LKPD). The development of the learning tool follows the model formulated by Kemp, Morrison, and Ross, consisting of nine development elements, namely instructional problems, student characteristics, task analysis, instructional objectives, sequence content, instructional strategies, instructional delivery, evaluation instruments, and instructional resources. The tool was tested on students in grade XI IPA1 at SMA Negeri 6 Pinrang. The data analysis results indicate that (i) the profile of contextual-based learning tools, including Lesson Implementation Plans, Student Learning Materials, and Student Activity Sheets, is valid and reliable; (ii) there is a significant improvement in students' critical thinking skills with an increase of 0.42, categorized as a moderate improvement; (iii) students' responses to the learning tool and the implementation of learning activities